Association between methane yield and microbiota abundance in the anaerobic digestion process: A meta-regression. (January 2021) - Ma, Guiling; Chen, Yanting; Ndegwa, Pius
Abstract: Anaerobic digestion (AD) is a bioprocess for extracting renewable bio-methane fuel from a variety of biomass substrates. A growing body of literature indicate that the structure of the microbiota community closely correlates with methane yield during AD. The correlations between methane yield and the relative abundance (RA) of microbial community, however, is mainly qualitative. The goal of this research was to collate the published data to determine the quantitative nature and extent of such correlations. Available literature on AD providing methane yields and microbiota RA, suitable for the random model, were gathered from the web of sciences and other available data bases for the meta-analyses and meta-regressions. In total, 1140-case studies, comprising 846 mesophilic and 246 thermophilic-AD processes, were used in the analysis. Data heterogeneity indicated that the RA of microbiota against methane yield of AD were different at different operating conditions. The main bacteria significantly determining methane yield, during AD processes, were Firmicutes and Bacteroidetes . A unit increase (%) in the RA of Firmicutes resulted in about 2.9 mL g −1 [VS] improvement in CH4 yield in non-stable mesophilic digesters, while the same improved CH4 yield by 4.5 mL g −1 [VS] in stable mesophilic digesters. In stable mesophilic AD, a unit increase (%) in the RA of Bacteroidetes significantly improved CH4 yield by 7.0 mL g −1 [VS] and by roughly 4.8 mL g −1 [VS] in non-stable mesophilic digesters. Significant decline in CH4 yields corresponded to increases in the RA of two bacteria phyla ( Actinobacteria and Proteobacteria ) commonly related to overloaded digesters. In this regard, a unit increase (%) in Actinobacteria indicated a significant reduction in CH4 yield (18.7 mL g −1 [VS]) in non-stable mesophilic digesters, while a unit increase (%) in Proteobacteria indicated around 4.9 mL g −1 [VS] decline in CH4 yield in stable mesophilic digesters. The major archaea significantly contributing to CH4 yield were Methanosarcina indicating CH4 yields improvements ranging from 2.0 to 3.0 mL g −1 [VS] for each percent increase in the RA of Methanosarcina, in either mesophilic or thermophilic digesters. The RA of other minor microbiota groups did not statistically correlate with CH4 yield. The HRT and OLR tended to positively correlate with the RA of Firmicutes, Bacteroidetes, and Methanosarcina . Graphical abstract: Image 1 Highlights: Firmicutes and Bacteroidetes were the main bacteria impacting CH4 yield. Methane yields were inversely correlated to the RA of Actinobacteria and Proteobacteria. The main archaea significantly contributing to CH4 yield was Methanosarcina. Acetoclastic and hydrogenotrophic methanogens complemented each other in CH4 production. The HRT and OLR tended to positively correlate with the RA of Firmicutes, Bacteroidetes, and Methanosarcina.